Point-of-care ultrasonography of carotid arteries in primary care: sensitivity and specificity of identification of carotid atherosclerosis and prevalence of carotid atherosclerosis in apparently healthy subjects with high and very high cardiovascular disease risk - Anej Kebrič; Marija Petek Šter; Anja Poljanšek Avsenak; Borut Jug (BMC Primary Care)
Abstract Background Cardiovascular diseases (CVDs) remain a major global health concern, contributing significantly to morbidity and mortality. The use of point-of-care ultrasonography (POCUS) in primary care has grown in popularity, offering a promising approach for early atherosclerosis detection. The objective was to investigate the sensitivity and specificity of family medicine physicians in identifying carotid atherosclerosis using POCUS and to determine the prevalence of carotid atherosclerosis in apparently healthy subjects with high or very high CVD risk. Methods A cross-sectional study was conducted from June 2023 to January 2024 across seven family medicine practices in Slovenia. The study included 199 participants aged 40-69, with high or very high CVD risk and no prior treatment with antilipemic drugs. Two participants were excluded due to insufficient quality of ultrasonographic recordings. Participants underwent POCUS of the carotid arteries to detect atherosclerotic plaques. Sensitivity and specificity were calculated against the assessments of a certified specialist in cardiology and vascular medicine. Results The study found a high prevalence (69.5% [62.6-75.9]) of carotid atherosclerosis among participants, with higher rates in males and older age groups. Sensitivity and specificity of POCUS for detecting carotid atherosclerosis were 96.4% [91.7-98.8] and 90.0% [79.5-96.2], respectively. Carotid atherosclerosis was more common in participants with very high CVD risk compared to those with high CVD risk. Conclusions Carotid atherosclerosis in apparently healthy subjects with high and very high CVD risk is much more prevalent than expected. POCUS of the carotid arteries is a highly sensitive and specific method for detecting carotid atherosclerosis in primary care. This method can significantly enhance early CVD risk assessment and intervention by family medicine practitioners. Trial registration ISRCTN registry as ISRCTN10591599 (registration date 26.07.2024).